There's such divinity doth hedge a king : selected essays of Nicolas Wyatt on royal ideology in Ugaritic and Old Testament literature /: selected essays of Nicolas Wyatt on royal ideology in Ugaritic and Old Testament literature. (2016) - Unknown
No abstract available